Crosstalk between human DC subsets promotes antibacterial activity and CD8+ T‐cell stimulation in response to bacille Calmette‐Guérin. Issue 1 (20th October 2013) - Lozza, Laura; Farinacci, Maura; Faé, Kellen; Bechtle, Marina; Stäber, Manuela; Dorhoi, Anca; Bauer, Mario; Ganoza, Christian; Weber, Stephan; Kaufmann, Stefan H.E.
<x xml:space="preserve">Abstract</x> To date, little is known about the unique contributions of specialized human DC subsets to protection against tuberculosis (TB). Here, we focus on the role of human plasmacytoid (p)DCs and myeloid (m)DCs in the immune response to the TB vaccine bacille Calmette‐Guérin (BCG). Ex vivo DC subsets from human peripheral blood were purified and infected with BCG expressing GFP to distinguish between infected and noninfected cells. BDCA‐1+ myeloid DCs were more susceptible than BDCA‐3+ mDCs to BCG infection. Plasmacytoid DCs have poor phagocytic activity but are equipped with endocytic receptors and can be activated by bystander stimulation. Consequently, the mutual interaction of the two DC subsets in response to BCG was analyzed. We found that pDCs were activated by BCG‐infected BDCA‐1+ mDCs to upregulate maturation markers and to produce granzyme B, but not IFN‐α. Reciprocally, the presence of activated pDCs enhanced mycobacterial growth control by infected mDCs and increased IL‐1β availability. The synergy between the two DC subsets promoted BCG‐specific CD8+ T‐cell stimulation and the role of BCG‐infected BDCA‐1+ mDCs could not be efficiently replaced by infected BDCA‐3+ mDCs in the crosstalk with pDCs. We conclude that mDC–pDC crosstalk should be exploited for rational design of next‐generation TB vaccines.